A Highly Conserved Protein of Unknown Function Is Required by Sinorhizobium meliloti for Symbiosis and Environmental Stress Protection - Davies, Bryan W. (American Society for Microbiology (ASM), 2008)
We report here the first characterization of the Sinorhizobium meliloti open reading frame SMc01113. The SMc01113 protein is a member of a highly conserved protein family, universal among bacteria. We demonstrate that the SMc01113 gene is absolutely required for S. meliloti symbiosis with alfalfa and also for the protection of the bacterium from a wide range of environmental stresses.